2008
DOI: 10.2478/s11687-008-0039-7
|View full text |Cite
|
Sign up to set email alerts
|

A check-list of parasites of percid fishes (Actinopterygii: Percidae) from the estuaries of the Polish coastal zone

Abstract: The present paper summarized data on parasites of percid fishes (Actinopterygii: Percidae), such as pike-perch, European perch and ruffe from estuaries of the Polish coastal zone are listed, based on published records and long-term surveys carried out by the author. Parasites are listed alphabetically, separately for each host and for each parasite group with notes on their location on the host and geographical distribution (with references). A total of 41 species (taxa) of parasites were recorded on pike-perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…; b Kuperman (1973); c Hoffmann et al (1986); d this study; e Ergens (1966); f Chubb (1964); g Andrews (1979); h Lucky & Navratil (1984); i Negele et al (1990); j Morozinska-Gogol (2013); k Dezfuli et al (2014); l Behrmann-Godel et al (2014); m Bylund & Pugachev (1989); n Morozinska-Gogol (2008). (Table I).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…; b Kuperman (1973); c Hoffmann et al (1986); d this study; e Ergens (1966); f Chubb (1964); g Andrews (1979); h Lucky & Navratil (1984); i Negele et al (1990); j Morozinska-Gogol (2013); k Dezfuli et al (2014); l Behrmann-Godel et al (2014); m Bylund & Pugachev (1989); n Morozinska-Gogol (2008). (Table I).…”
mentioning
confidence: 81%
“…The recent arrival in Lake Constance of an invasive gill worm of the genus Ancyrocephalus (Monogenea) prompted morphological and genetic studies that identified the species as Ancyrocephalus percae (Behrmann-Godel et al, 2014). This parasite has a pan-European distribution (Andrews, 1979;Bylund & Pugachev, 1989;Morozinska-Gogol, 2008), and is not generally known for causing severe harm to its P. fluviatilis hosts (Andrews, 1979). Normally, A. percae infects only the gills of P. fluviatilis (Ergens, 1966) but in Lake Constance the adult parasites appear to actively migrate from the gills to the isthmus, where they cause deep, oval to round lesions (Behrmann-Godel et al, 2014).…”
mentioning
confidence: 99%
“…The pike tapeworm Triaenophorus nodulosus is one of the most common cestodes in Eurasian perch and also in the American yellow perch Perca flavescens, both of which it infects as second intermediate hosts, at notable fitness cost [14,19, 20]. The detriment to host fitness may be partly attributed to the energetic costs of mounting and maintaining an immune response to infection [21, 22].…”
Section: Methodsmentioning
confidence: 99%
“…The perch is a long-lived species (maximum recorded age of 21 years, usually to about 6 years (Kottelat and Freyhof 2007), with a generation time of approximately 3 years, reproducing once a year in spring (Craig 2000). Due to its broad distribution, the wide range of habitats used and the many food sources utilized, a high number of parasite species from various orders have been described for the species (e.g., Craig 2000; Morozinska-Gogol 2008; Behrmann-Godel 2013). In previous studies Michel et al.…”
Section: Introductionmentioning
confidence: 99%
“…The perch is a long-lived species (maximum recorded age of 21 years, usually to about 6 years (Kottelat and Freyhof 2007), with a generation time of approximately 3 years, reproducing once a year in spring (Craig 2000). Due to its broad distribution, the wide range of habitats used and the many food sources utilized, a high number of parasite species from various orders have been described for the species (e.g., Craig 2000;Morozinska-Gogol 2008;Behrmann-Godel 2013). In previous studies Michel et al (2009) andOppelt andBehrmann-Godel (2012) found a high variability of MHC class II ß genes in the perch with at least five expressed loci, and numerous alleles and established a genotyping method via reference strand conformation analysis (RSCA) which allows for high-throughput individual MHC genotyping (Lenz et al 2009).…”
Section: Introductionmentioning
confidence: 99%